The Workplace Bullying in Nurses: A Psychometric Propertises of Iranian Version of Negative Acts Questionnaire-Revised - Kalantari, Soheyla; Sharif Nia, Hamid; Ghana, Samieh; Goudarzian, Amir Hossein; Chehrehgosha, Maryam (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Workplace bullying is a persistent amount of negative conduct which one individual is subjected to by another, and it is emotionally and psychologically aggravating. Nurses are exposed to a greater risk of bullying, due to their direct contact with patients and their associates. The present study aims to investigate the factor structure of Iranian version of Negative Acts Questionnaire-Revised. Methods: The present methodological study was conducted amongst 400 nurses working in various hospitals affiliated to the Gorgan University of Medical Sciences, over a three month period in 2017. Construct validity of the questionnaire was assessed, and its reliability was also verified for internal consistency, and construct reliability. Results: Exploratory factor analysis led to the extraction of the following three factors: Physically intimidating bullying, person-related bullying, and work-related bullying. The model’s good fit indices confirmed the workplace bullying in nursing tool as follows: PCFI= 0.767, PNFI= 0.721, CMIN/DF= 2.325, RMSEA= 0.081, AGFI= 0.815, IFI= 0.912, and CFI= 0.918. The convergent validity and discriminant validity of the construct of workplace bullying in nursing as well as its internal consistency and construct reliability (>0.7) were confirmed. Conclusions: The present study results showed that the three-factor construct of workplace bullying in nursing has good validity and reliability. Given its favorable psychometric properties, this questionnaire can be effective in assessing the incidence rate of workplace bullying in the nursing profession.